A Review of Chitosan in Oral Drug Delivery Formulations (Asian Journal of Pharmaceutics (AJP), 2024)
In recent decades, the utility of nanoformulations as medication delivery systems has grown. It is not alwaysthe best option due to gastrointestinal distress, restricted inadequate absorption, and solubility. The impactof the early hepatic transit is one of the biggest obstacles that drugs must get past to have a therapeuticeffect. These materials have attracted a lot of attention because studies have shown that oral delivery can besignificantly enhanced by controlled-release systems that use nanoparticles (NPs) made of naturally derivedbiodegradable polymers. Chitosan (CS) has several applications and qualities in the pharmaceutical andmedical industries. The traditional medication delivery method has been completely transformed by NPs’capacity to modify molecules and their structures. In the current environment, CS because of their smallsize, NPs are a valuable tool for novel drug delivery systems. The process of ionotropic gelation is not theonly one used in this field; alternative techniques include solvent evaporation, polyelectrolyte complex,emulsification solvent diffusion, emulsification cross-linking, and microemulsion. Numerous drug deliveryapplications, such as CS NPs have been found to be beneficial for a range of utilization, encompassingmucosal and controlled administration of drugs, tissue engineering, delivery of non-viral genes, vaccines,ocular drugs, electrodeposition, delivery of drugs that target the brain, enhancement of stability, and efficientdelivery of insulin.